2020
DOI: 10.1101/2020.02.25.20027615
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stochastic discrete epidemic modeling of COVID-19 transmission in the Province of Shaanxi incorporating public health intervention and case importation

Abstract: Before the lock-down of Wuhan/Hubei/China, on January 23 rd 2020, a large number of individuals infected by COVID-19 moved from the epicenter Wuhan and the Hubei province due to the Spring Festival, resulting in an epidemic in the other provinces including the Shaanxi province. The epidemic scale in Shaanxi was comparatively small and with half of cases being imported from the epicenter. Based on the complete epidemic data including the symptom onset time and transmission chains, we calculate the control repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
3
10
1
Order By: Relevance
“…It also could be seen that our estimated basic reproduction number before 11 February 2020 was slightly higher than that of some previous studies [15,18,[41][42][43]57]. This might be mainly caused by the following two reasons.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…It also could be seen that our estimated basic reproduction number before 11 February 2020 was slightly higher than that of some previous studies [15,18,[41][42][43]57]. This might be mainly caused by the following two reasons.…”
Section: Discussioncontrasting
confidence: 71%
“…Therefore, to find more effective control efforts, the peak arrival time and the trend of the COVID-19 epidemic in the mainland of China should be predicted with a well-designed model [32,33]. Many studies have estimated the reproduction number in the early phase of COVID-19 outbreak in China [32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…In the 22 countries or cities, before the lockdown, the basic reproduction numbers were between 1.3884-4.1926; after the lockdown, the basic reproduction numbers were between 1.2141-3.7829; the average basic reproduction numbers were between 1.5286-3.8067. The results were in good agreement with many existing results [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The basic reproduction numbers in the 22 countries or cities decreased significantly after the lockdown, which suggested that lockdown measures indeed suppressed the epidemics.…”
Section: Resultssupporting
confidence: 89%
“…Many studies estimated the basic reproduction number in the early phase of COVID-19 outbreak [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Some results indicated that the basic reproduction number was greater than 3, [32] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the increased awareness on the use of personal protective measures against COVID-19 after noticing the unknown pneumonia outbreak in Wuhan in early January through social media. Similar transmission dynamics were also reported in Shaanxi province (Tang et al, 2020).…”
Section: Discussionsupporting
confidence: 85%